Prognostic Accuracy of VITRO Score in Predicting the Mortality in patient with Decompensated Liver Cirrhosis - Abid Ali, Salman Javed, Muhammad Haseeb Nawaz, Aniq Fayyaz, Qasim Zia, Najam-us-Sehar Saeed (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Cirrhosis of the liver is a widespread chronic illness that kills more people from non-malignant diseases than any other condition. In the case of cirrhosis, the liver has sustained long-term damage and is unable to operate normally. The VITRO score is a noninvasive instrument that can forecast whether cirrhotic patients would experience problems. Objective: To determine the prognostic accuracy of VITRO score in predicting the mortality in patient with decompensated liver cirrhosis Material & Methods: Study Design: Descriptive Study Setting: Liver Clinic, Services Hospital, Lahore Duration: 06 months January 2022 to June 2022. One Hundred Ninety cirrhotic patients were recruited after meeting the inclusion criteria. Both informed consent and demographic data were collected. Blood samples were drawn and were sent to a certain facility in order to test for VWF-Ag and thrombocyte count. The VITRO-score was estimated by dividing the VWF-Ag to thrombocyte count. Patient followed for 3 months after which it was determined whether patients survived or died of cirrhosis complications. Results: The mean age of the patients was 51.42±9.98 years, 103(54.50%) were male. The mean VITRO score of the patients was 6.15±6.08. The VITRO scores the prediction of mortality was noted in 148(77.9%) patients. The sensitivity was 96.08%, specificity was 28.78%, and diagnostic accuracy of VITRO score was 46.84% for assessment of mortality taking mortality occurred within 3 months as gold standard. Practical implication: The prognosis of patients could be improved by using accurate prognostic scoring systems to assist clinicians in earlier diagnosis and therapy selection. Conclusion: According to this study the prognostic accuracy of VITRO score in predicting the mortality is approximately 50% in patient with decompensated liver cirrhosis, however the sensitivity of it is very high Keywords: Prognostic Accuracy, VITRO score, Mortality, Cirrhosis, decompensated liver disease